Transmission of SARS-CoV-2, Required Developments in Research and Associated Public Health Concerns - Khan, Suliman; Liu, Jianbo; Xue, Mengzhou (Frontiers in Medicine, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is rapidly spreading across the world to cause thousands of mortalities each day. Poor responses from the authorities to the spread of infection, lack of effective measures for prevention, unavailability of promising treatment options and sufficient diagnostic options have created an alarming for the world. The transmission routes from human to human of SARS-CoV-2 can be the direct transmission, droplet inhalation transmission, contact transmission, transmission through saliva, and transmission via fetal–oral routes. Due to the asymptomatic spread of SARS-CoV-2’s, developing control and prevention measures is challenging. Implementing proper strategies addressing the infection control and clinical supplies, understanding the mechanism associated with pathogenesis, advancing in preventive measures and effective treatment and diagnostic options are necessary to control the ongoing pandemic and eradicate COVID-19 infection. In this article, we briefly discuss the features, entry mechanism, infectiousness, and health consequences related to the COVID-19 outbreak.